2017
DOI: 10.1111/jfpp.13193
|View full text |Cite
|
Sign up to set email alerts
|

Radiant heat treatments for corn drying and decontamination

Abstract: Freshly harvested corn at moisture content of 24% wet basis (w.b.) was intermittently dried with infrared (IR) at intensities 2.39, 3.78, and 5.55 kW/m2 for 30, 50, and 180 s to safe storage‐moisture content of 13% (w.b). Microbial load reduction, energy use and corn sensory and pasting qualities were evaluated. Experiments were carried out at product‐to‐emitter gap size of 450 mm. Increasing IR intensity from 2.39 to 5.55 kW/m2 resulted in average microbial load reductions of 2.6 and 2.9 log CFU/g at 180 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…Likewise, low intensities of the selected IR wavelengths showed significant reduction in mold load after incorporating a tempering step. In agreement with the current result, Wilson, Okeyo, et al (2017) reported that IR treatment of corn followed by tempering at 50 C for 4 hr resulted in 3.8-4.5 log CFU/g of mold reduction. However, statistical analysis showed that there was no interaction effect (p > .05) between intensity of both broadband and selected IR after incorporating a tempering step.…”
Section: Effect Of Incorporating a Tempering Step After Ir Wavelengsupporting
confidence: 93%
See 3 more Smart Citations
“…Likewise, low intensities of the selected IR wavelengths showed significant reduction in mold load after incorporating a tempering step. In agreement with the current result, Wilson, Okeyo, et al (2017) reported that IR treatment of corn followed by tempering at 50 C for 4 hr resulted in 3.8-4.5 log CFU/g of mold reduction. However, statistical analysis showed that there was no interaction effect (p > .05) between intensity of both broadband and selected IR after incorporating a tempering step.…”
Section: Effect Of Incorporating a Tempering Step After Ir Wavelengsupporting
confidence: 93%
“…IR heating has been linked with the merits of higher energy transfer rate, shorter duration of drying, milder environmental footprints, and better or comparable product quality than convective heated air treatments (Wang et al, ). In addition, IR heating has the potential to simultaneously dry and inactivate microbes and their spores on grains (Khir, Pan, Salim, Hartsough, & Mohamed, ; Pan et al, ; Tanaka et al, ; Wang et al, ; Wilson, Okeyo, Olatunde, & Atungulu, ; Yang et al, ). For industrial application purposes, IR energy emission can be realized through design of IR emitters such as catalytic or ceramic emitters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Irradiation using gamma, ultraviolet (UV), or electron beam radiation has been demonstrated to reduce PEDV load by 3-log (Trudeau et al, 2016). Wilson et al (2015Wilson et al ( , 2016 demonstrated the feasibility of using infrared radiation to decontaminate raw pet food ingredients; depending on initial moisture content of the ingredients, infrared heating intensity, and tempering duration, up to 3-log of mycotoxigenic fungi was reduced.…”
Section: Physical Methodsmentioning
confidence: 99%